2016
DOI: 10.1096/fj.201600502r
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β‐catenin pathway in tissue injury: roles in pathology and therapeutic opportunities for regeneration

Abstract: The Wnt/β-catenin pathway is an evolutionarily conserved set of signals with critical roles in embryonic and neonatal development across species. In mammals the pathway is quiescent in many organs. It is reactivated in response to injury and is reported to play complex and contrasting roles in promoting regeneration and fibrosis. We review the current understanding of the role of the Wnt/β-catenin pathway in injury of various mammalian organs and discuss the current advances and potential of Wnt inhibitory the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 178 publications
3
86
0
Order By: Relevance
“…Several pathways regulate skeletal muscle fibrosis . Of these, TGF‐β and Wnt‐signaling mechanisms are considered as the key players in fibrosis . Canonical Wnt signaling is upregulated during aging as well as after tissue injury and is recognized as a key player in kidney, liver, myocardial, and pulmonary fibrosis .…”
Section: Discussionmentioning
confidence: 99%
“…Several pathways regulate skeletal muscle fibrosis . Of these, TGF‐β and Wnt‐signaling mechanisms are considered as the key players in fibrosis . Canonical Wnt signaling is upregulated during aging as well as after tissue injury and is recognized as a key player in kidney, liver, myocardial, and pulmonary fibrosis .…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the present findings, a previous transcriptomic study of Val66Met mice found the Wnt signaling pathway dysregulated in BDNF Met/Met mice (Wang et al, ). Wnt/β‐catenin canonical pathway regulates many cellular processes such as development during embryogenesis, maintenance of tissue homeostasis, and regeneration in the adult (Bastakoty & Young, ; Grigoryan et al, ). In the adult hippocampus, Wnt signaling regulates synaptic plasticity, dendritic morphogenesis, synaptogenesis, long‐term potentiation, and learning and memory (Dickins & Salinas, ; Fortress & Frick, ; Rosso & Inestrosa, ).…”
Section: Discussionmentioning
confidence: 99%
“…) and our findings confirm a role for periostin as a novel marker in penile fibrosis. Targeted antifibrotic therapy has been shown to reduce fibrosis and improve organ function (Bastakoty and Young ).…”
Section: Discussionmentioning
confidence: 99%